Antennal uridine diphosphate (UDP)‐glycosyltransferases in a pest insect: diversity and putative function in odorant and xenobiotics clearance. Issue 5 (4th April 2014) - Bozzolan, F.; Siaussat, D.; Maria, A.; Durand, N.; Pottier, M.‐A.; Chertemps, T.; Maïbèche‐Coisne, M.
Abstract Uridine diphosphate UDP‐glycosyltransferases (UGTs) are detoxification enzymes widely distributed within living organisms. They are involved in the biotransformation of various lipophilic endogenous compounds and xenobiotics, including odorants. Several UGTs have been reported in the olfactory organs of mammals and involved in olfactory processing and detoxification within the olfactory mucosa but, in insects, this enzyme family is still poorly studied. Despite recent transcriptomic analyses, the diversity of antennal UGTs in insects has not been investigated. To date, only three UGT cDNAs have been shown to be expressed in insect olfactory organs. In the present study, we report the identification of eleven putative UGTs expressed in the antennae of the model pest insect Spodoptera littoralis. Phylogenetic analysis revealed that these UGTs belong to five different families, highlighting their structural diversity. In addition, two genes, UGT40R3 and UGT46A6, were either specifically expressed or overexpressed in the antennae, suggesting specific roles in this sensory organ. Exposure of male moths to the sex pheromone and to a plant odorant differentially downregulated the transcription levels of these two genes, revealing for the first time the regulation of insect UGTs by odorant exposure. Moreover, the specific antennal gene UGT46A6 was upregulated by insecticide topical application on antennae, suggesting its role in the protection of the olfactory organ towards xenobiotics. This work highlights the structural and functional diversity of UGTs within this highly specialized tissue.